2011
DOI: 10.1590/s0102-86502011000600016
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and hematologic consequences of colectomy associated to hepatectomy in rats

Abstract: PURPOSE:To investigate the influence of partial colectomy associated with hepatectomy on the biodistribution of the 99m Tc-phytate, on metabolic parameters, as well as labeling and morphology of red blood cells. METHODS: Wistar rats were distributed into three groups (each with six), nominated as colectomy, colectomy+hepatectomy and sham. In the 30 th postoperative day all rats were injected with 99mTc-phytate 0.1mL i.v. (radioactivity 0.66 MBq). After 15 minutes, liver sample was harvested and weighed. Percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Despite the colon resection was not performed in the present study, we intend to use this model in the near future in this research line. In other studies, impaired liver regeneration after bowel resection has been demonstrated [25][26][27][28] , confirming the findings of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the colon resection was not performed in the present study, we intend to use this model in the near future in this research line. In other studies, impaired liver regeneration after bowel resection has been demonstrated [25][26][27][28] , confirming the findings of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…However, in EG, despite the levels of leukocytes being normal, this was not confirmed in the macroscopic analysis, which showed the presence of infection. Carvalho et al 13 , when investigating the Table 4 Table 4 Table 4 Table 4 Table 4 -Microscopic analysis of specimens from animals submitted to hepatectomy with hemostasis promoted by TachoSil ® versus electrocautery in the 14 th postoperative day. hematological and metabolic consequences of colectomy combined with partial hepatectomy in rats, found a significantly greater increase in the levels of AST, ALT and alkaline phosphatase in the colectomy and hepatectomy group than in the colectomy alone group, suggesting that hepatectomy was responsible for such enzyme elevation.…”
Section: Classification Classification Classification Classification mentioning
confidence: 99%